The affective embeddings of gacha games: Aesthetic assemblages and the mediated expression of the self - WOODS, Orlando (Institutional Knowledge at Singapore Management University, 2024)
This paper argues that the motivations for investing money in gacha games can be a function of the affective embedding of players within the game, and the game within broader circuits of cultural affinity and appeal. Whilst research on gacha games – and the specific role of loot boxes therein – has emphasised their associations with gambling, I contend that affect is another trigger that can motivate seemingly irrational playing behaviours. The affective embeddings of gacha games motivate players to curate aesthetic assemblages of virtual content that enable the mediated expression of the self. Drawing on qualitative data generated amongst young Singapore-based players of gacha games, I explore how the acquisition of characters, skins and collections can be motivated by the emotional payoff that comes from relationality rather than gambling.